Ukryte kamery Stanisława Barei - Pławuszewski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The article is the introduction to Stanisław Bareja’s master’s thesis Zagadnienia realizacji filmów z ukrytej kamery stanowiących część telewizyjnych programów rozrywkowych [Candid camera filmmaking for entertainment TV programs, 1974]. It points out the American background of the candid camera genre, like Allen Funt’s production, which started in 1948 [ABC], and specifies the main focus of Bareja’ thesis, e.g. multi-stage process of making candid camera clips for Polish TV and the mechanics of making audience laugh.